Perianal leiomyoma - Bruna Fernandes dos Santos; Lucas Rodrigues Boarini; Pietro Dadalto Oliveira; Fernanda Belotti Formiga; Galdino José Sitonio Formiga; Anderson da Costa Lino Costa (Journal of Coloproctology, 2017)
Leiomyomas are smooth muscle tumors and may occur in places where these fibers are present, while the anorectal location is rare. They are commonly incidental imaging findings and in most cases, patients are asymptomatic. The therapeutic recommendation is tumor resection and postoperative follow-up. Case report: a 38-year-old Black woman had, one year ago, a swelling in perianal right region, which showed slow and progressive growth. She denied bowel habit alterations, local pain, hematochezia, or tenesmus. Proctologic examination showed a fibroelastic, regular, mobile, painless nodule measuring 10 cm at its largest diameter in the right perianal region, next to the anal verge. The soft tissue ultrasound image identified a solid, hypoechoic, and discreetly vascularized nodule in the perianal, superficial right gluteal region that did not reach the adjacent muscles. A complete resection of perineal tumor was carried out in the ventral position. Histological and immunohistochemical analyses disclosed a leiomyoma with a positive finding for actin smooth muscle and negative for desmin. She is currently asymptomatic and undergoing outpatient follow-up. Resumo: Os leiomiomas são tumores da musculatura lisa podendo ocorrer nos locais onde essas fibras estão presentes, sendo rara a localização anorretal. Na maioria dos casos os pacientes são assintomáticos, sendo comumente achados de exame de imagem. A recomendação terapêutica é a ressecção tumoral e o seguimento pós-operatório. Relato do caso: mulher, 38 anos, negra. Há um ano, apresentou abaulamento em região perianal direita, de crescimento lento e progressivo. Negava alteração do hábito intestinal, dor local, hematoquezia, puxo ou tenesmo. Ao exame proctológico, apresentava nodulação fibroelástica, regular, móvel, indolor, com 10 cm de diâmetro em região perianal à direita, próxima à borda anal. Realizou ultrassonografia de partes moles que identificou imagem nodular, sólida, hipoecogênica e discreta vascularização em parte superficial perianal e glútea direita, não envolvendo musculatura adjacente. Foi submetida à ressecção completa do tumor via perineal, em posição ventral. O laudo histológico e imuno-histoquímico revelou leiomioma, com achado positivo para actina de músculo liso e negativo para desmina. Atualmente está assintomática, em seguimento ambulatorial. Keywords: Gastrointestinal neoplasia, Gastrointestinal stromal tumors, Leiomyoma, Anal canal, Palavras-chave: Neoplasias gastrointestinais, Tumores do estroma gastrointestinal, Leiomioma, Canal anal